Thermoelectricity and phase change energy storage super high performance concrete and preparation method thereof

CN122977801APending Publication Date: 2026-10-27JIANGSU QITIAN ELECTRIC POWER CONSTR GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611196256.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

现有导电混凝土通常采用在混凝土中直接添加碳纤维、石墨烯等导电填料的方式,但导电填料与相变材料相互独立存在,缺乏功能耦合,难以实现电热转换和相变储能的协同效应

Benefits of technology

(1)通过碳纳米管泡沫骨架与有机相变材料的复合,制备了兼具导电功能和相变储能功能的复合微球。碳纳米管泡沫骨架的三维连续网络结构既作为导电通路,通电时产生焦耳热,又作为导热通路,将热量快速传递至相变材料,还作为相变材料的承载骨架,通过毛细管力锁定熔融相变材料防止泄漏,实现了结构-功能一体化设计,避免了传统方案中导电填料与相变材料独立添加所带来的相容性和分散性问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977801A_ABST
    Figure CN122977801A_ABST
Patent Text Reader

Abstract

The application discloses a kind of thermoelectricity synergic phase change energy storage super high performance concrete and preparation method thereof, belong to building material technical field, the concrete includes by weight fraction: sulphoaluminate cement 600-900 parts, fly ash 200-400 parts, silica ash 150-300 parts, granulated blast furnace slag powder 250-450 parts, nano alumina 10-50 parts, water 280-420 parts, pottery sand 800-1200 parts, electrically conductive phase change energy storage composite microsphere 350-600 parts, polycarboxylic acid water reducing agent 6-18 parts, copper-plated steel fiber 30-100 parts.Electrically conductive phase change energy storage composite microsphere is constituted by carbon nanotube foam framework and organic phase change material filled in its pore.The application uses the above-mentioned one kind of thermoelectricity synergic phase change energy storage super high performance concrete and preparation method thereof, realizes the integration of phase change energy storage and electrically conductive heat conducting function integration, with excellent mechanical property, electrically conductive heat conducting performance and temperature regulation capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and in particular to a thermoelectric synergistic phase change energy storage ultra-high performance concrete and its preparation method. Background Technology

[0002] As the construction industry moves towards low-carbon and intelligent development, the performance requirements for building materials are increasing. Ultra-high performance concrete (UHPC), with its ultra-high strength, excellent durability, and toughness, is widely used in bridge engineering, high-rise buildings, and marine engineering. However, traditional UHPC still has the following shortcomings: Conventional UHPCs are inert heat-carrying materials, resulting in significant temperature fluctuations inside buildings when ambient temperatures change. This increases energy consumption for temperature control equipment such as air conditioners, hindering building energy conservation. In recent years, researchers have attempted to introduce phase change energy storage materials (PCS) into UHPCs to regulate indoor temperature through the heat storage / release properties of PCS. However, existing PCS UHPCs suffer from poor encapsulation stability of PCS materials and incompatible compatibility with the concrete matrix, hindering the full realization of PCS energy storage effects. Furthermore, the addition of PCS materials often negatively impacts the mechanical properties of concrete. With the development of special applications such as smart buildings, self-melting snow pavements, and electromagnetic shielding, higher demands are placed on the electrical and thermal conductivity of concrete. Existing conductive concrete typically involves directly adding conductive fillers such as carbon fiber and graphene to the concrete. However, the conductive fillers and PCS materials exist independently, lacking functional coupling, making it difficult to achieve a synergistic effect between electrothermal conversion and PCS energy storage. Carbon nanotubes have excellent electrical and thermal conductivity and mechanical properties. However, in the current technology, carbon nanotubes are mostly dispersed in concrete matrix with the help of dispersants, which has the problems of severe agglomeration and uneven dispersion, making it difficult to give full play to their performance advantages.

[0003] Therefore, there is an urgent need to provide an ultra-high performance concrete that combines phase change energy storage with electrical and thermal conductivity, and whose components have good compatibility, in order to solve the above-mentioned technical problems. Summary of the Invention

[0004] The purpose of this invention is to provide a thermoelectric synergistic phase change energy storage ultra-high performance concrete and its preparation method. By combining carbon nanotube foam skeleton with organic phase change materials, the phase change energy storage function and the electrical and thermal conductivity functions are integrated in the same microsphere. At the same time, the mechanical properties and durability of the concrete are guaranteed by the synergistic design of sulfoaluminate cement-based cementitious material system and lightweight ceramic sand.

[0005] This invention provides a thermoelectric synergistic phase change energy storage ultra-high performance concrete and its preparation method, comprising the following raw material components by weight: Sulfoaluminate cement 600-900 parts, fly ash 200-400 parts, silica fume 150-300 parts, granulated blast furnace slag powder 250-450 parts, nano alumina 10-50 parts, water 280-420 parts, ceramic sand 800-1200 parts, conductive phase change energy storage composite microspheres 350-600 parts, polycarboxylate superplasticizer 6-18 parts, copper-plated steel fiber 30-100 parts; Among them, the conductive phase change energy storage composite microspheres include a carbon nanotube foam skeleton and an organic phase change material filled in the pores of the carbon nanotube foam skeleton. The carbon nanotube foam skeleton is a three-dimensional continuous network structure, and the organic phase change material is encapsulated in the pores of the carbon nanotube foam skeleton. The conductive phase change energy storage composite microspheres combine phase change energy storage and conductivity. The carbon nanotube foam skeleton generates Joule heat when energized, and the Joule heat is transferred to the organic phase change material in the pores for storage.

[0006] Preferably, the organic phase change material is a fatty acid ester phase change material, which is selected from at least one of methyl palmitate, butyl stearate, and methyl laurate.

[0007] Preferably, the phase change temperature of the fatty acid ester phase change material is 20-28℃, and the latent heat of phase change is 160-190J / g.

[0008] Preferably, the carbon nanotube foam skeleton is a foam structure assembled from multi-walled carbon nanotubes by chemical vapor deposition, with a porosity of 85-95% and a pore size distribution of 50-500 nm.

[0009] Preferably, the particle size of the conductive phase change energy storage composite microspheres is 100-500 μm, and the mass fraction of organic phase change material in the composite microspheres is 60-80%.

[0010] Preferably, the particle size of the ceramic sand is 0.5-2.5 mm, and the apparent density is 1200-1600 kg / m³. 3 The copper-plated steel fibers are 6-15mm in length, 0.1-0.3mm in diameter, and have an aspect ratio of 40-100.

[0011] A method for preparing ultra-high performance concrete with thermoelectric synergistic phase change energy storage as described above includes the following steps: S1. Preparation of conductive phase change energy storage composite microspheres: Carbon nanotube foam skeletons are impregnated in molten organic phase change material for 2-8 hours under vacuum conditions of -0.08 to -0.1 MPa and temperature 10-30°C higher than the melting point of the organic phase change material, so that the organic phase change material fills the pores of the carbon nanotube foam skeleton. After cooling, crushing and sieving, conductive phase change energy storage composite microspheres are obtained. S2. Preparation of gelatinous mixture: Sulfoaluminate cement, fly ash, silica fume, granulated blast furnace slag powder and nano alumina are dry-mixed in proportion for 8-15 minutes to obtain a cementitious mixture; S3. Preparation of dispersion: The polycarboxylate superplasticizer was dissolved in water and stirred until evenly dispersed to obtain a dispersion. S4, Mixed Molding: Dry mix the ceramic sand and S2 cementitious mixture for 3-6 minutes, add the dispersion of S3 and wet mix for 2-4 minutes, then add the conductive phase change energy storage composite microspheres and copper-plated steel fibers of S1, and stir at a low speed of 60-150 rpm for 5-10 minutes to obtain ultra-high performance concrete mixture. After pouring and curing, the thermoelectric synergistic phase change energy storage ultra-high performance concrete is obtained.

[0012] Preferably, in S1, the carbon nanotube foam skeleton is prepared by using multi-walled carbon nanotubes as raw materials, which are acidified and then subjected to chemical vapor deposition at 900-1100℃ using methane as a carbon source, so that the carbon nanotubes cross-link and assemble to form a three-dimensional foam structure.

[0013] Preferably, in S1, the vacuum impregnation temperature is 40-80℃, and the vacuum impregnation process is accompanied by ultrasonic oscillation treatment with an ultrasonic frequency of 20-50kHz and an ultrasonic power of 100-300W.

[0014] Preferably, in S4, the curing is steam curing, and the steam curing conditions are: curing at 60-85℃ and relative humidity ≥95% for 36-60 hours.

[0015] Therefore, the present invention employs the above-mentioned thermoelectric synergistic phase change energy storage ultra-high performance concrete and its preparation method, which has the following beneficial effects: (1) Composite microspheres with both conductive and phase change energy storage functions were prepared by combining carbon nanotube foam skeleton with organic phase change material. The three-dimensional continuous network structure of carbon nanotube foam skeleton serves as a conductive path, generating Joule heat when energized, as a thermal path, rapidly transferring heat to the phase change material, and as a supporting skeleton for the phase change material, locking the molten phase change material with capillary force to prevent leakage. This achieves an integrated structure-function design, avoiding the compatibility and dispersion problems caused by the independent addition of conductive filler and phase change material in traditional schemes.

[0016] (2) Fatty acid ester phase change materials are used as energy storage media. They have high latent heat of phase change and good wettability and chemical compatibility with carbon nanotube foam skeleton. Under the assistance of vacuum impregnation process and ultrasonic oscillation, the phase change material can be fully filled into the nanoscale pores of the skeleton, with a filling rate of 60-80%, which effectively ensures the energy storage density of the microspheres.

[0017] (3) A quaternary composite cementitious system of sulfoaluminate cement-fly ash-silica fume-granulated blast furnace slag powder is adopted. The densest packing is achieved through the gradient distribution of particle size of each component. At the same time, the pozzolanic reaction of fly ash and slag powder is used to improve the later strength, so that the concrete can maintain ultra-high performance under the premise of low carbon emissions. The addition of nano alumina further fills the nanoscale pores, improving the density and elastic modulus of the concrete.

[0018] (4) The porous structure of ceramic sand is used to achieve the internal curing effect and reduce the self-shrinkage of concrete; the addition of copper-plated steel fibers forms a multi-scale conductive system of microsphere conductive network and fiber conductive pathway, which works synergistically with carbon nanotube foam skeleton to enhance the electrical and thermal conductivity of concrete. The synergistic cooperation among the functional components ensures the excellent mechanical properties and durability of concrete while realizing the thermoelectric phase change energy storage function.

[0019] (5) The preparation method adopts a step-by-step strategy of first preparing functional microspheres and then preparing concrete. The preparation of functional microspheres and the preparation of concrete are independent of each other, with a wide process window and strong operational controllability. During the concrete preparation process, low-speed stirring and a specific feeding sequence are used to protect the structural integrity of functional microspheres to the maximum extent, ensuring the stability and repeatability of product performance.

[0020] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0021] Figure 1 This is a bar chart comparing the mechanical properties of concrete samples from Examples 1-3 and Comparative Examples 1-4 of the present invention, which describe a thermoelectric synergistic phase change energy storage ultra-high performance concrete and its preparation method. Figure 2 This is a comparison of the electrical and thermal conductivity of concrete samples from Examples 1-3 and Comparative Examples 1-4 of the present invention, which describe a thermoelectric synergistic phase change energy storage ultra-high performance concrete and its preparation method. Detailed Implementation

[0022] To better understand the above technical solutions, a detailed description of the solutions will be provided below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0023] The terminology used in the embodiments of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The singular forms “a,” “the,” and “the” as used in the embodiments of this invention and the appended claims are also intended to include the plural forms, and “multiple” generally includes at least two unless the context clearly indicates otherwise.

[0024] It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that an article or device that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such an article or device. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the article or device that includes said element.

[0025] This invention provides a thermoelectric synergistic phase change energy storage ultra-high performance concrete and its preparation method, comprising the following raw material components by weight: Sulfoaluminate cement 600-900 parts, fly ash 200-400 parts, silica fume 150-300 parts, granulated blast furnace slag powder 250-450 parts, nano alumina 10-50 parts, water 280-420 parts, ceramic sand 800-1200 parts, conductive phase change energy storage composite microspheres 350-600 parts, polycarboxylate superplasticizer 6-18 parts, copper-plated steel fiber 30-100 parts; The conductive phase change energy storage composite microspheres comprise a carbon nanotube foam framework and an organic phase change material filling the pores of the carbon nanotube foam framework. The carbon nanotube foam framework is a three-dimensional continuous network structure, and the organic phase change material is encapsulated within the pores of the carbon nanotube foam framework. The carbon nanotube foam framework is a foam structure assembled from multi-walled carbon nanotubes via chemical vapor deposition, with a porosity of 85-95% and a pore size distribution of 50-500 nm. The particle size of the conductive phase change energy storage composite microspheres is 100-500 μm, and the mass fraction of the organic phase change material in the composite microspheres is 60-80%.

[0026] The conductive phase change energy storage composite microspheres combine phase change energy storage and conductivity. The carbon nanotube foam skeleton generates Joule heat when energized, and the Joule heat is transferred to the organic phase change material in the pores for storage.

[0027] Specifically, sulfoaluminate cement is characterized by rapid hardening and early strength, enabling it to hydrate quickly at relatively low temperatures and achieve high strength, which is beneficial for the early stability of phase change materials (PCMs) in concrete. Simultaneously, the concentrated heat release and low peak temperature of sulfoaluminate cement reduce thermal shock to PCMs, preventing leakage or failure of PCMs during the high-temperature hydration stage of cement. Furthermore, sulfoaluminate cement has significantly lower carbon emissions than silicate cement, aligning with the development direction of low-carbon green buildings. Fly ash, silica fume, and granulated blast furnace slag powder, as auxiliary cementitious materials, form a multi-component composite cementitious system with sulfoaluminate cement. Through the gradient distribution of particle sizes and the synergistic effect of pozzolanic reaction, the bulk density and long-term mechanical properties of concrete are improved.

[0028] Carbon nanotube foam frameworks are three-dimensional continuous network structures assembled from multi-walled carbon nanotubes via chemical vapor deposition. They possess extremely high porosity and specific surface area, providing ample storage space for organic phase change materials. Simultaneously, carbon nanotubes themselves exhibit excellent electrical and thermal conductivity, with a resistivity of approximately 10⁻⁶. -4 -10 -3 With a thermal conductivity exceeding 3000 W / (m·K) in Ω·cm, its three-dimensional continuous network structure can form complete conductive and thermal pathways within the microspheres. When the microspheres are energized, the carbon nanotube foam skeleton generates Joule heating, which is rapidly transferred through the three-dimensional network to the organic phase change material within the pores for storage, achieving functional coupling of "electrothermal conversion and phase change energy storage." This structural design enables a single microsphere to simultaneously possess conductive and energy storage functions, unlike traditional methods that add conductive fillers and phase change materials independently.

[0029] Nano-alumina possesses higher hardness and elastic modulus, enabling it to more effectively fill nanoscale pores in concrete, thereby improving concrete density and elastic modulus. Simultaneously, nano-alumina exhibits excellent thermal conductivity, with a thermal conductivity coefficient of approximately 30-40 W / (m·K), which can assist carbon nanotube foam skeletons in constructing thermal conduction pathways, enhancing the heat storage / release efficiency of phase change materials. Furthermore, nano-alumina demonstrates superior chemical stability in alkaline environments compared to nano-SiO2, making it more compatible with the chemical environment of sulfoaluminate cement systems.

[0030] The organic phase change material is a fatty acid ester phase change material, which is selected from at least one of methyl palmitate, butyl stearate, and methyl laurate. The phase change temperature of the fatty acid ester phase change material is 20-28℃, and the latent heat of phase change is 160-190 J / g.

[0031] Specifically, fatty acid ester phase change materials (PCCs) possess a suitable phase change temperature range, making them suitable for building energy conservation applications. Furthermore, fatty acid ester PCCs exhibit excellent wettability with carbon nanotube foam frameworks, enabling them to fully fill the nanoscale pores of the framework during vacuum impregnation, and their low viscosity contributes to improved filling efficiency. Compared to paraffin-based PCCs, fatty acid esters demonstrate better biodegradability and environmental friendliness; they are also less corrosive and have better compatibility with metal fibers and cement matrices.

[0032] The particle size of ceramic sand is 0.5-2.5mm, and the apparent density is 1200-1600kg / m³. 3 The copper-plated steel fibers are 6-15mm in length, 0.1-0.3mm in diameter, and have an aspect ratio of 40-100.

[0033] Specifically, ceramsite sand is a porous, lightweight material with a rough surface and high water absorption rate, enabling it to form good mechanical interlocking with cement paste and improve the bond strength in the interfacial transition zone. Simultaneously, the porous structure of ceramsite sand has a certain "internal curing" effect, slowly releasing water during cement hydration, promoting full hydration of the cementitious materials, and reducing the autogenous shrinkage of concrete. Furthermore, the low density of ceramsite sand helps reduce the self-weight of concrete, and its synergistic effect with the carbon nanotube foam skeleton can further improve the specific strength and functional density of concrete. Copper-plated steel fibers, with a copper layer on their surface, have a higher interfacial bonding strength with the cement matrix than ordinary steel fibers, enabling them to more effectively transfer and disperse stress, improving the tensile strength and crack resistance of concrete. At the same time, the copper layer has good electrical conductivity; the overlapping of copper-plated steel fibers in concrete can form auxiliary conductive pathways, synergizing with the three-dimensional conductive network of conductive phase change energy storage composite microspheres to construct a multi-scale conductive system of "microsphere conductive network + fiber conductive pathways," further reducing the resistivity of concrete and improving electrothermal conversion efficiency.

[0034] A method for preparing ultra-high performance concrete with thermoelectric synergistic phase change energy storage as described above includes the following steps: S1. Preparation of conductive phase change energy storage composite microspheres: A carbon nanotube foam framework is impregnated in a molten organic phase change material (OPCW) for 2-8 hours under vacuum conditions of -0.08 to -0.1 MPa and a temperature 10-30°C higher than the melting point of the OPCW. This allows the OPCW to fill the pores of the carbon nanotube foam framework. After cooling, pulverizing, and sieving, conductive phase change energy storage composite microspheres are obtained. The vacuum impregnation temperature is 40-80°C, and ultrasonic oscillation is performed during the process at a frequency of 20-50 kHz and a power of 100-300 W. The carbon nanotube foam framework is prepared by using multi-walled carbon nanotubes as raw materials. After acidification, chemical vapor deposition is performed at 900-1100°C using methane as a carbon source, causing the carbon nanotubes to cross-link and assemble to form a three-dimensional foam structure.

[0035] S2. Preparation of gelatinous mixture: Sulfoaluminate cement, fly ash, silica fume, granulated blast furnace slag powder and nano alumina are dry-mixed in proportion for 8-15 minutes to obtain a cementitious mixture; S3. Preparation of dispersion: The polycarboxylate superplasticizer was dissolved in water and stirred until evenly dispersed to obtain a dispersion. S4, Mixed Molding: Dry mix the ceramic sand with S2 cementitious mixture for 3-6 minutes, add the dispersion of S3 and wet mix for 2-4 minutes, then add the conductive phase change energy storage composite microspheres and copper-plated steel fibers of S1, and stir at a low speed of 60-150 rpm for 5-10 minutes to obtain ultra-high performance concrete mixture. After pouring and molding, it is cured by steam curing. The steam curing conditions are: 60-85℃ and relative humidity ≥95% for 36-60 hours to obtain thermoelectric synergistic phase change energy storage ultra-high performance concrete.

[0036] Specifically, vacuum impregnation is a key process step in the preparation of conductive phase change energy storage composite microspheres. Under vacuum conditions, air is extracted from the pores of the carbon nanotube foam framework, creating a negative pressure environment. When the impregnation temperature is higher than the melting point of the phase change material, the molten organic phase change material is forcibly drawn into the pores of the foam framework under the combined action of capillary force and external atmospheric pressure, achieving full filling of the phase change material within the nanoscale pores. The temperature and vacuum level of vacuum impregnation directly affect the filling effect: too low a temperature results in high viscosity and poor flowability of the phase change material; too high a temperature may lead to oxidation or degradation of the phase change material. An optimal vacuum level and temperature range (-0.08 to -0.1 MPa, 10-30°C above the melting point) ensures the best filling efficiency and uniformity.

[0037] Ultrasonic oscillation-assisted vacuum impregnation utilizes the cavitation effect and mechanical vibration generated by the ultrasonic oscillation to ensure sufficient contact between the molten phase change material and the carbon nanotube foam framework. This promotes the penetration of the phase change material into the finer pores within the foam framework, improving the filling rate and uniformity. Simultaneously, ultrasonic oscillation helps eliminate air bubbles generated during the filling process, preventing the formation of cavities within the microspheres and ensuring the structural integrity and phase change energy storage density of the composite microspheres. Preferred ultrasonic frequencies (20-50 kHz) and power (100-300 W) effectively promote filling without damaging the microstructure of the carbon nanotube foam framework.

[0038] The preparation method involves controlling the sequence and stirring speed. First, the cementitious materials are dry-mixed to ensure thorough and uniform mixing of all powder components. Then, the dispersion is added for wet mixing to fully hydrate the cement particles. Finally, conductive phase-change energy storage composite microspheres and copper-plated steel fibers are added, and the mixture is stirred at a low speed of 60-150 rpm. This is to avoid damaging the carbon nanotube foam skeleton structure and the integrity of the microspheres due to high-speed stirring, while also preventing fiber agglomeration. This specific sequence and comprehensive control of stirring speed are crucial to ensuring the uniform distribution of functional components and structural integrity in the concrete.

[0039] To provide a clearer and more detailed description of the thermoelectric synergistic phase change energy storage ultra-high performance concrete and its preparation method provided by the embodiments of the present invention, the following description will be based on specific embodiments.

[0040] Example 1 This embodiment provides a thermoelectric synergistic phase change energy storage ultra-high performance concrete, which comprises the following raw material components by weight: 600 parts of sulfoaluminate cement, 200 parts of fly ash, 150 parts of silica fume, 250 parts of granulated blast furnace slag powder, 10 parts of nano-alumina, 280 parts of water, 800 parts of ceramic sand, 350 parts of conductive phase change energy storage composite microspheres, 6 parts of polycarboxylate superplasticizer, and 30 parts of copper-plated steel fiber.

[0041] The preparation method of conductive phase change energy storage composite microspheres is as follows: (1) Preparation of carbon nanotube foam skeleton: Multi-walled carbon nanotubes are used as raw materials. After acid treatment, they are placed in a chemical vapor deposition reactor and chemical vapor deposition is carried out at 900℃ with methane as carbon source. The carbon nanotubes are cross-linked and assembled to form a three-dimensional foam structure with a porosity of 85% and a pore size distribution of 50-500nm.

[0042] (2) Vacuum impregnation and filling of phase change material: Methyl palmitate, a fatty acid ester phase change material with a phase change temperature of 22℃ and a latent heat of phase change of 180J / g, is heated to a molten state. Carbon nanotube foam skeleton is impregnated in the molten fatty acid ester. Vacuum impregnation is carried out for 2 hours under the conditions of vacuum degree of -0.08MPa and temperature of 15℃ higher than the melting point of phase change material, so that organic phase change material fills the pores of carbon nanotube foam skeleton. After cooling, crushing and sieving, conductive phase change energy storage composite microspheres are obtained. The microsphere particle size is 100-500μm, and the mass fraction of organic phase change material in composite microspheres is 60%.

[0043] The ultra-high performance concrete with thermoelectric synergistic phase change energy storage in this embodiment is prepared through the following steps: S1. Prepare conductive phase change energy storage composite microspheres according to the above method; S2. Mix 600 parts of sulfoaluminate cement, 200 parts of fly ash, 150 parts of silica fume, 250 parts of granulated blast furnace slag powder and 10 parts of nano alumina in a specific ratio for 8 minutes to obtain a cementitious mixture. S3. Dissolve 6 parts of polycarboxylate superplasticizer in 280 parts of water, stir and disperse evenly to obtain a dispersion; S4. Dry mix 800 parts of ceramic sand with the cementitious mixture of S2 for 3 minutes, add the dispersion of S3 and wet mix for 2 minutes, then add 350 parts of conductive phase change energy storage composite microspheres and 30 parts of copper-plated steel fiber of S1, and stir at a low speed of 60 rpm for 5 minutes to obtain ultra-high performance concrete mixture. After casting and molding, steam cure for 36 hours at 60℃ and relative humidity ≥95% to obtain thermoelectric synergistic phase change energy storage ultra-high performance concrete.

[0044] Example 2 This embodiment provides a thermoelectric synergistic phase change energy storage ultra-high performance concrete, which comprises the following raw material components by weight: 750 parts of sulfoaluminate cement, 300 parts of fly ash, 225 parts of silica fume, 350 parts of granulated blast furnace slag powder, 30 parts of nano-alumina, 350 parts of water, 1000 parts of ceramic sand, 475 parts of conductive phase change energy storage composite microspheres, 12 parts of polycarboxylate superplasticizer, and 65 parts of copper-plated steel fiber.

[0045] The preparation method of conductive phase change energy storage composite microspheres is as follows: (1) Preparation of carbon nanotube foam skeleton: Multi-walled carbon nanotubes are used as raw materials. After acid treatment, they are placed in a chemical vapor deposition reactor and chemical vapor deposition is carried out at 1000℃ with methane as carbon source. The carbon nanotubes are cross-linked and assembled to form a three-dimensional foam structure with a porosity of 90% and a pore size distribution of 50-500nm.

[0046] (2) Vacuum impregnation and filling of phase change material: The fatty acid ester phase change material, butyl stearate, with a phase change temperature of 25℃ and a latent heat of phase change of 175J / g, is heated to a molten state. The carbon nanotube foam skeleton is impregnated in the molten fatty acid ester. Vacuum impregnation is carried out for 5 hours under the conditions of vacuum degree of -0.09MPa and temperature of 20℃ higher than the melting point of the phase change material. During the vacuum impregnation process, ultrasonic oscillation treatment is carried out with an ultrasonic frequency of 35kHz and an ultrasonic power of 200W, so that the organic phase change material fills the pores of the carbon nanotube foam skeleton. After cooling, crushing and sieving, conductive phase change energy storage composite microspheres are obtained. The microsphere particle size is 100-500μm, and the mass fraction of organic phase change material in the composite microspheres is 70%.

[0047] The ultra-high performance concrete with thermoelectric synergistic phase change energy storage in this embodiment is prepared through the following steps: S1. Prepare conductive phase change energy storage composite microspheres according to the above method; S2. Mix 750 parts of sulfoaluminate cement, 300 parts of fly ash, 225 parts of silica fume, 350 parts of granulated blast furnace slag powder and 30 parts of nano alumina in a certain proportion for 12 minutes to obtain a cementitious mixture. S3. Dissolve 12 parts of polycarboxylate superplasticizer in 350 parts of water, stir and disperse evenly to obtain a dispersion. S4. Dry mix 1000 parts of ceramic sand with the cementitious mixture of S2 for 5 minutes, add the dispersion of S3 and wet mix for 3 minutes, then add 475 parts of conductive phase change energy storage composite microspheres and 65 parts of copper-plated steel fiber of S1, and stir at a low speed of 105 rpm for 8 minutes to obtain ultra-high performance concrete mixture. After casting and molding, steam cure for 48 hours at 72℃ and relative humidity ≥95% to obtain thermoelectric synergistic phase change energy storage ultra-high performance concrete.

[0048] Example 3 This embodiment provides a thermoelectric synergistic phase change energy storage ultra-high performance concrete, which comprises the following raw material components by weight: 900 parts of sulfoaluminate cement, 400 parts of fly ash, 300 parts of silica fume, 450 parts of granulated blast furnace slag powder, 50 parts of nano-alumina, 420 parts of water, 1200 parts of ceramic sand, 600 parts of conductive phase change energy storage composite microspheres, 18 parts of polycarboxylate superplasticizer, and 100 parts of copper-plated steel fiber.

[0049] The preparation method of conductive phase change energy storage composite microspheres is as follows: (1) Preparation of carbon nanotube foam skeleton: Multi-walled carbon nanotubes are used as raw materials. After acid treatment, they are placed in a chemical vapor deposition reactor and chemical vapor deposition is carried out at 1100℃ with methane as carbon source. The carbon nanotubes are cross-linked and assembled to form a three-dimensional foam structure with a porosity of 95% and a pore size distribution of 50-500nm.

[0050] (2) Vacuum impregnation and filling of phase change material: Methyl laurate, a fatty acid ester phase change material, with a phase change temperature of 26℃ and a latent heat of phase change of 190J / g, was heated to a molten state. Carbon nanotube foam skeleton was impregnated in the molten fatty acid ester. Vacuum impregnation was carried out for 8 hours under the conditions of vacuum degree of -0.1MPa and temperature 30℃ higher than the melting point of phase change material. Ultrasonic oscillation treatment was carried out during the vacuum impregnation process. The ultrasonic frequency was 50kHz and the ultrasonic power was 300W, so that the organic phase change material filled the pores of the carbon nanotube foam skeleton. After cooling, crushing and sieving, conductive phase change energy storage composite microspheres were obtained. The microsphere particle size was 100-500μm, and the mass fraction of organic phase change material in the composite microspheres was 80%.

[0051] The ultra-high performance concrete with thermoelectric synergistic phase change energy storage in this embodiment is prepared through the following steps: S1. Prepare conductive phase change energy storage composite microspheres according to the above method; S2. Mix 900 parts of sulfoaluminate cement, 400 parts of fly ash, 300 parts of silica fume, 450 parts of granulated blast furnace slag powder and 50 parts of nano alumina in a specific ratio and dry mix for 15 minutes to obtain a cementitious mixture. S3. Dissolve 18 parts of polycarboxylate superplasticizer in 420 parts of water, stir and disperse evenly to obtain a dispersion. S4. Dry mix 1200 parts of ceramic sand with the cementitious mixture of S2 for 6 minutes, add the dispersion of S3 and wet mix for 4 minutes, then add 600 parts of conductive phase change energy storage composite microspheres and 100 parts of copper-plated steel fiber of S1, and stir at a low speed of 150 rpm for 10 minutes to obtain ultra-high performance concrete mixture. After casting and molding, steam cure for 60 hours at 85℃ and relative humidity ≥95% to obtain thermoelectric synergistic phase change energy storage ultra-high performance concrete.

[0052] Comparative Example 1 This comparative example provides a conventional ultra-high performance concrete, which comprises the following raw material components by weight: 750 parts silicate cement, 300 parts fly ash, 225 parts silica fume, 350 parts granulated blast furnace slag powder, 30 parts nano-SiO2, 350 parts water, 1000 parts quartz sand, 12 parts polycarboxylate superplasticizer, and 65 parts ordinary steel fiber.

[0053] Conventional ultra-high performance concrete is prepared through the following steps: Silicate cement, fly ash, silica fume, granulated blast furnace slag powder, and nano-SiO2 were dry-mixed for 12 minutes to obtain a cementitious mixture. Polycarboxylate superplasticizer was dissolved in water and stirred to disperse evenly to obtain a dispersion. Quartz sand was dry-mixed with the cementitious mixture for 5 minutes, the dispersion was added and wet-mixed for 3 minutes, then ordinary steel fibers were added and stirred at a low speed of 105 rpm for 8 minutes to obtain a concrete mixture. After being poured and molded, it was steam-cured for 48 hours at 72℃ and relative humidity ≥95% to obtain conventional ultra-high performance concrete.

[0054] The difference between this comparative example and Example 2 is that: conductive phase change energy storage composite microspheres were not added, nano-alumina was not added, ceramic sand was not added, sulfoaluminate cement was not used, and copper-plated steel fibers were not used.

[0055] Comparative Example 2 This comparative example provides a conventional phase change energy storage ultra-high performance concrete, which comprises the following raw material components by weight: 750 parts of sulfoaluminate cement, 300 parts of fly ash, 225 parts of silica fume, 350 parts of granulated blast furnace slag powder, 30 parts of nano-alumina, 350 parts of water, 1000 parts of ceramic sand, 475 parts of ordinary phase change microcapsules (core material is paraffin wax, wall material is polymethyl methacrylate), 12 parts of polycarboxylate superplasticizer, and 65 parts of copper-plated steel fiber.

[0056] Ordinary phase change energy storage ultra-high performance concrete is prepared through the following steps: Sulfoaluminate cement, fly ash, silica fume, granulated blast furnace slag powder, and nano-alumina were dry-mixed for 12 minutes to obtain a cementitious mixture. Polycarboxylate superplasticizer was dissolved in water and stirred to disperse evenly to obtain a dispersion. Ceramic sand was dry-mixed with the cementitious mixture for 5 minutes, and the dispersion was added and wet-mixed for 3 minutes. Then, ordinary phase change microcapsules and copper-plated steel fibers were added, and the mixture was stirred at a low speed of 105 rpm for 8 minutes to obtain a concrete mixture. After being poured and molded, the mixture was steam-cured at 72℃ and relative humidity ≥95% for 48 hours to obtain ordinary phase change energy storage ultra-high performance concrete.

[0057] The difference between this comparative example and Example 2 is that ordinary phase change microcapsules are used instead of conductive phase change energy storage composite microspheres, and the phase change material is not combined with carbon nanotube foam skeleton.

[0058] Comparative Example 3 This comparative example provides a phase change energy storage ultra-high performance concrete without conductive function, which includes the following raw material components by weight: 750 parts of sulfoaluminate cement, 300 parts of fly ash, 225 parts of silica fume, 350 parts of granulated blast furnace slag powder, 30 parts of nano-alumina, 350 parts of water, 1000 parts of ceramic sand, 475 parts of non-conductive phase change energy storage composite microspheres (composed of porous silica foam skeleton filled with butyl stearate), 12 parts of polycarboxylate superplasticizer, and 65 parts of copper-plated steel fiber.

[0059] Ultra-high performance concrete with non-conductive phase change energy storage is prepared through the following steps: Sulfoaluminate cement, fly ash, silica fume, granulated blast furnace slag powder, and nano-alumina were dry-mixed for 12 minutes to obtain a cementitious mixture. Polycarboxylate superplasticizer was dissolved in water and stirred to disperse evenly to obtain a dispersion. Ceramic sand was dry-mixed with the cementitious mixture for 5 minutes, and the dispersion was added and wet-mixed for 3 minutes. Then, non-conductive phase change energy storage composite microspheres and copper-plated steel fibers were added, and the mixture was stirred at a low speed of 105 rpm for 8 minutes to obtain a concrete mixture. After being poured and molded, the mixture was steam-cured at 72℃ and relative humidity ≥95% for 48 hours to obtain a non-conductive phase change energy storage ultra-high performance concrete.

[0060] The difference between this comparative example and Example 2 is that a porous silica foam skeleton is used instead of a carbon nanotube foam skeleton.

[0061] Comparative Example 4 This comparative example provides a conductive phase change energy storage ultra-high performance concrete using a conventional silicate cement system, comprising the following raw material components by weight: 750 parts silicate cement, 300 parts fly ash, 225 parts silica fume, 350 parts granulated blast furnace slag powder, 30 parts nano alumina, 350 parts water, 1000 parts quartz sand, 475 parts conductive phase change energy storage composite microspheres (same as in Example 2), 12 parts polycarboxylate superplasticizer, and 65 parts copper-plated steel fiber.

[0062] The conductive phase change energy storage ultra-high performance concrete of this comparative example was prepared through the following steps: Silicate cement, fly ash, silica fume, granulated blast furnace slag powder, and nano-alumina were dry-mixed for 12 minutes to obtain a cementitious mixture. Polycarboxylate superplasticizer was dissolved in water and stirred to disperse evenly to obtain a dispersion. Quartz sand was dry-mixed with the cementitious mixture for 5 minutes, and the dispersion was added and wet-mixed for 3 minutes. Then, conductive phase change energy storage composite microspheres and copper-plated steel fibers were added and stirred at a low speed of 105 rpm for 8 minutes to obtain a concrete mixture. After being poured and molded, it was steam-cured for 48 hours at 72℃ and relative humidity ≥95% to obtain conductive phase change energy storage ultra-high performance concrete.

[0063] The difference between this comparative example and Example 2 is that silicate cement is used instead of sulfoaluminate cement, and quartz sand is used instead of ceramic sand.

[0064] Performance testing: The concrete samples from Examples 1-3 and Comparative Examples 1-4 were made into standard specimens and their performance was tested according to relevant standards.

[0065] Compressive strength and flexural strength tests were conducted in accordance with GB / T 31387—2025 "Ultra-High Performance Concrete". The size of the compressive specimen was 100mm×100mm×100mm, and the size of the flexural specimen was 100mm×100mm×400mm. The 28-day compressive strength and 28-day flexural strength were tested.

[0066] Resistivity test: The resistivity of concrete specimens was tested using the four-probe method (Winner probe method). The specimen size was 100mm×100mm×100mm.

[0067] Phase change latent heat test: Differential scanning calorimetry (DSC) was used to test the actual latent heat of phase change materials in conductive phase change energy storage composite microspheres and concrete samples.

[0068] Thermal conductivity test: The thermal conductivity of the concrete specimens was tested using the transient plane heat source method (Hot Disk method).

[0069] Temperature fluctuation amplitude test: Concrete samples were made into 100mm×100mm×100mm cube specimens and placed in a temperature-adjustable test chamber. The ambient temperature was set to cycle between 18-30℃, with a heating rate of 1℃ / min and a cooling rate of 1℃ / min. Each cycle lasted 120 minutes, and a total of 5 cycles were performed. The change in the internal core temperature of the specimen over time was recorded. The temperature fluctuation amplitude after the 3rd-5th cycles stabilized was calculated, which is the difference between the maximum and minimum internal temperature of the specimen. The test results are shown in Tables 1-4.

[0070] Table 1 Mechanical properties of different concrete specimens

[0071] As shown in Table 1, the compressive and flexural strengths of Examples 1-3 are significantly better than those of Comparative Examples 1 and 4. Comparative Example 1, using a conventional silicate cement system without the addition of phase change energy storage composite microspheres, has the lowest mechanical properties. Comparative Example 4, although containing conductive phase change energy storage composite microspheres, uses a silicate cement and quartz sand system, resulting in significantly lower mechanical properties than Example 2, which uses a sulfoaluminate cement and ceramic sand system. Compared to Comparative Example 3, Comparative Example 3 uses a non-conductive silica foam skeleton, and its mechanical properties are slightly better than Example 2 due to the higher stiffness of the silica foam skeleton, but it sacrifices conductivity. Example 2 maintains excellent conductivity while achieving a compressive strength of 172 MPa and a flexural strength of 19.2 MPa. In Example 3, the mechanical properties are further improved with the increase of the dosage of each functional component.

[0072] Table 2 Electrical and thermal conductivity properties of different concrete specimens

[0073] As shown in Table 2, the resistivity of Examples 1-3 is significantly lower than that of Comparative Examples 1-3, indicating that the three-dimensional continuous conductive network of the carbon nanotube foam skeleton greatly improves the conductivity of the concrete. Comparative Example 3 uses a non-conductive silica foam skeleton; although the phase change material loading is the same as in Example 2, its resistivity is as high as 7.80 Ω·m, making it almost non-conductive. This demonstrates that the carbon nanotube foam skeleton is key to achieving conductivity. Comparative Example 2 uses ordinary phase change microcapsules, which also exhibit poor conductivity. Comparative Example 4 uses a conventional silicate cement system, and its conductivity is similar to that of Example 2, indicating that the conductive phase change energy storage composite microspheres can effectively perform conductive functions in different cementitious systems, but their mechanical properties are somewhat reduced.

[0074] The thermal conductivity of Examples 1-3 is also significantly higher than that of Comparative Examples 1-3. The carbon nanotube foam skeleton also serves as a heat conduction channel, effectively improving the thermal conductivity of concrete.

[0075] Table 3. Phase change energy storage performance of different concrete samples

[0076] As shown in Table 3, the actual latent heat of phase change (LCH) of the conductive phase change energy storage composite microspheres in Examples 1-3 is close to the theoretical value. The vacuum impregnation method achieves efficient filling of the phase change material in the carbon nanotube foam skeleton, and the phase change material maintains good energy storage activity in the composite microspheres. Comparative Example 2 uses ordinary paraffin-based phase change microcapsules, and the actual LCH is only 118 J / g, far lower than the theoretical value. Ordinary microcapsules have the problem of phase change material leakage during concrete preparation and curing. Comparative Example 3 uses a silica foam skeleton to fill the phase change material, and the LCH is similar to that of Example 2. The porous skeleton vacuum impregnation method itself can achieve a high phase change material loading rate, but the silica foam skeleton does not have conductive function. The LCH of Comparative Example 4 is similar to that of Example 2, indicating that the carbon nanotube foam skeleton composite phase change material can maintain stable energy storage performance in different cementing systems.

[0077] Table 4 Temperature control performance of different concrete specimens

[0078] As shown in Table 4, the temperature fluctuation range of Examples 1-3 was significantly smaller than that of Comparative Examples 1 and 2. Comparative Example 1, which did not add any phase change material, exhibited the largest temperature fluctuation. Although Comparative Example 2 added ordinary phase change microcapsules, the actual latent heat of phase change was low due to partial leakage of the phase change material during concrete preparation and curing, resulting in limited temperature control and a temperature fluctuation range of 4.2℃. The temperature fluctuation range of Example 2 was smaller than that of Comparative Example 3. Although the latent heat of phase change in Comparative Example 3 was slightly lower than that in Example 2, the difference in temperature control performance between the two mainly stemmed from the difference in latent heat of phase change. More importantly, Comparative Example 3 lacked electrical conductivity and could not achieve thermoelectric synergy. The temperature fluctuation range of Comparative Example 4 was similar to that of Example 2. The temperature control function of the carbon nanotube foam skeleton composite phase change material was effectively utilized in different cementing systems, but as mentioned earlier, the mechanical properties of Comparative Example 4 decreased.

[0079] Based on the above test results, the thermoelectric synergistic phase change energy storage ultra-high performance concretes of Examples 1-3 of this invention exhibit excellent comprehensive performance in terms of mechanical properties, electrical conductivity, thermal conductivity, phase change energy storage performance, and temperature regulation performance. Compared with the conventional UHPC of Comparative Example 1, this invention endows concrete with thermoelectric synergistic phase change energy storage function while maintaining ultra-high performance; compared with the ordinary phase change microcapsule UHPC of Comparative Example 2, the conductive phase change energy storage composite microspheres of this invention achieve efficient encapsulation of phase change materials and integration of conductive function through carbon nanotube foam skeleton, resulting in higher utilization rate of phase change materials and better conductivity; compared with the non-conductive silica foam skeleton UHPC of Comparative Example 3, the carbon nanotube foam skeleton of this invention endows concrete with excellent electrical conductivity while ensuring phase change energy storage performance, achieving true thermoelectric synergy; compared with the conventional silicate cement system of Comparative Example 4, the sulfoaluminate cement-ceramic sand system of this invention further improves mechanical properties while ensuring conductivity and energy storage functions. This invention achieves a multifunctional integration of ultra-high performance concrete with thermoelectric synergistic phase change energy storage, ultra-high mechanical properties, and excellent electrical and thermal conductivity by combining carbon nanotube foam skeleton with phase change materials and synergistic design of sulfoaluminate cement-based cementitious material system with functional components.

[0080] Therefore, this invention employs the aforementioned thermoelectric synergistic phase change energy storage ultra-high performance concrete and its preparation method. By combining a carbon nanotube foam skeleton with an organic phase change material, composite microspheres with both conductive and phase change energy storage functions are prepared. The three-dimensional continuous network structure of the carbon nanotube foam skeleton serves as both a conductive pathway, generating Joule heat when energized, and a thermal pathway, rapidly transferring heat to the phase change material. It also acts as a supporting skeleton for the phase change material, using capillary forces to lock the molten phase change material and prevent leakage. This achieves an integrated structure-function design, avoiding the compatibility and dispersion problems caused by the independent addition of conductive fillers and phase change materials in traditional solutions. Fatty acid ester-based phase change materials are used as the energy storage medium, possessing high latent heat of phase change and good wettability and chemical compatibility with the carbon nanotube foam skeleton. Under vacuum impregnation and ultrasonic oscillation assistance, the phase change material can fully fill the nanoscale pores of the skeleton, achieving a filling rate of 60-80%, effectively ensuring the energy storage density of the microspheres.

[0081] A quaternary composite cementitious system consisting of sulfoaluminate cement, fly ash, silica fume, and granulated blast furnace slag powder is employed. The gradient distribution of particle sizes among the components achieves the densest packing, while the pozzolanic reaction of fly ash and slag powder enhances later-stage strength, enabling the concrete to maintain ultra-high performance while maintaining low carbon emissions. The addition of nano-alumina further fills the nanoscale pores, improving the concrete's density and elastic modulus. The porous structure of ceramic sand achieves an internal curing effect, reducing the concrete's autogenous shrinkage. The addition of copper-plated steel fibers forms a multi-scale conductive system with microsphere conductive networks and fiber conductive pathways, synergistically enhancing the concrete's electrical and thermal conductivity with the carbon nanotube foam skeleton. The synergistic cooperation among the functional components achieves thermoelectric phase change energy storage while ensuring the concrete's excellent mechanical properties and durability.

[0082] The preparation method employs a step-by-step strategy of first preparing functional microspheres and then mixing concrete. The preparation of functional microspheres and the mixing of concrete are independent of each other, resulting in a wide process window and strong operational controllability. During the concrete mixing process, low-speed mixing and a specific order of adding materials are used to maximize the protection of the structural integrity of the functional microspheres, ensuring the stability and repeatability of product performance.

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A thermoelectric synergistic phase change energy storage ultra-high performance concrete, characterized in that, The following raw material components are included by weight: Sulfoaluminate cement 600-900 parts, fly ash 200-400 parts, silica fume 150-300 parts, granulated blast furnace slag powder 250-450 parts, nano alumina 10-50 parts, water 280-420 parts, ceramic sand 800-1200 parts, conductive phase change energy storage composite microspheres 350-600 parts, polycarboxylate superplasticizer 6-18 parts, copper-plated steel fiber 30-100 parts; Among them, the conductive phase change energy storage composite microspheres include a carbon nanotube foam skeleton and an organic phase change material filling the pores of the carbon nanotube foam skeleton. The carbon nanotube foam skeleton is a three-dimensional continuous network structure, and the organic phase change material is encapsulated in the pores of the carbon nanotube foam skeleton.

2. The ultra-high performance concrete with thermoelectric synergistic phase change energy storage according to claim 1, characterized in that, The organic phase change material is a fatty acid ester phase change material, which is selected from at least one of methyl palmitate, butyl stearate, and methyl laurate.

3. The ultra-high performance concrete with thermoelectric synergistic phase change energy storage according to claim 1, characterized in that, The phase transition temperature of fatty acid ester phase change materials is 20-28℃, and the latent heat of phase transition is 160-190J / g.

4. The ultra-high performance concrete with thermoelectric synergistic phase change energy storage according to claim 1, characterized in that, The carbon nanotube foam framework is a foam structure assembled from multi-walled carbon nanotubes by chemical vapor deposition, with a porosity of 85-95% and a pore size distribution of 50-500 nm.

5. The ultra-high performance concrete with thermoelectric synergistic phase change energy storage according to claim 1, characterized in that, The particle size of the conductive phase change energy storage composite microspheres is 100-500 μm, and the mass fraction of organic phase change material in the composite microspheres is 60-80%.

6. The ultra-high performance concrete with thermoelectric synergistic phase change energy storage according to claim 1, characterized in that, The particle size of ceramic sand is 0.5-2.5mm, and the apparent density is 1200-1600kg / m³. 3 The copper-plated steel fibers are 6-15mm in length, 0.1-0.3mm in diameter, and have an aspect ratio of 40-100.

7. A method for preparing ultra-high performance concrete with thermoelectric synergistic phase change energy storage as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Preparation of conductive phase change energy storage composite microspheres: Carbon nanotube foam skeletons are impregnated in molten organic phase change material for 2-8 hours under vacuum conditions of -0.08 to -0.1 MPa and temperature 10-30°C higher than the melting point of the organic phase change material, so that the organic phase change material fills the pores of the carbon nanotube foam skeleton. After cooling, crushing and sieving, conductive phase change energy storage composite microspheres are obtained. S2. Preparation of gelatinous mixture: Sulfoaluminate cement, fly ash, silica fume, granulated blast furnace slag powder and nano alumina are dry-mixed in proportion for 8-15 minutes to obtain a cementitious mixture; S3. Preparation of dispersion: The polycarboxylate superplasticizer was dissolved in water and stirred until evenly dispersed to obtain a dispersion. S4, Mixed Molding: Dry mix the ceramic sand and S2 cementitious mixture for 3-6 minutes, add the dispersion of S3 and wet mix for 2-4 minutes, then add the conductive phase change energy storage composite microspheres and copper-plated steel fibers of S1, and stir at a low speed of 60-150 rpm for 5-10 minutes to obtain ultra-high performance concrete mixture. After pouring and curing, the thermoelectric synergistic phase change energy storage ultra-high performance concrete is obtained.

8. The method for preparing ultra-high performance concrete with thermoelectric synergistic phase change energy storage according to claim 7, characterized in that, In S1, the carbon nanotube foam skeleton is prepared by using multi-walled carbon nanotubes as raw materials, which are acidified and then subjected to chemical vapor deposition at 900-1100℃ using methane as a carbon source, so that the carbon nanotubes cross-link and assemble to form a three-dimensional foam structure.

9. The method for preparing ultra-high performance concrete with thermoelectric synergistic phase change energy storage according to claim 7, characterized in that, In S1, the vacuum impregnation temperature is 40-80℃, and the vacuum impregnation process is accompanied by ultrasonic oscillation treatment with an ultrasonic frequency of 20-50kHz and an ultrasonic power of 100-300W.

10. The method for preparing ultra-high performance concrete with thermoelectric synergistic phase change energy storage according to claim 7, characterized in that, In S4, the curing method is steam curing. The steam curing conditions are: 60-85℃ and relative humidity ≥95% for 36-60 hours.